Factors Influencing Work-Life Flexibility In Multinational Companies In Malaysia: The Mediating Role Of Individual Absorptive Capacity And Moderating Role Of Digital Proficiency - Ravi, Ushvanya (2024)
This study focuses on analysing the factors that impact work-life flexibility in multinational corporations (MNCs) in Malaysia. The study utilizes theories from the Resource-Based View and Dynamic Capabilities, to investigate the relationship between training and development, career development, organisation development climate, and emotional intelligence. It aims to determine their effect on an employee's work-life flexibility.